Collapses without measurements - Burgos, María Esther (European Journal of Applied Sciences, 2022)
Abstract In quantum mechanics the state vector evolves in a predictable and continuous way, according to the Schrödinger equation; only if a measurement takes place, the Schrödinger evolution is interrupted. Transitions between stationary states (transitions BSS) are accounted for time dependent perturbation theory (TDPT). It is often ignored that this theory requires measurements. As measurements demand either the intervention of an observer or the interaction between the quantum system with a measuring device, billions of observers and/or measuring devices would be necessary at every small corner of the universe where transitions BSS take place. Nevertheless, there is no evidence of their existence. We are thus led to conclude that transitions BSS are the result of causes different from the measurements required in TDPT. In the spontaneous projection approach, the version of quantum mechanics which we uphold, collapses to the stationary states result from the tendency of the system to jump to the eigenstates of the constants of the motion.